Technological Andragogical Content Knowledge (Tack) Training to Improve The Professional Competency of Equal Education Tutors - Solfema, Solfema; Ismaniar, Ismaniar; Sunati, Vevi; Gusmanti, Reza (Universitas Negeri Padang, 2024)
In the rapidly evolving digital era, the world of education is undergoing significant changes that require tutors to master content andragogy technology. Adult learners have unique characteristics compared to children, such as rich life experiences, family and work responsibilities, and different motivations for learning. Therefore, training in content andragogy technology is crucial for tutors to design and deliver material that is relevant, flexible, and tailored to the needs of adult learners. This technology enables the use of interactive and engaging digital tools that can enhance learning engagement and motivation. Additionally, such training helps tutors develop the digital skills of learners, which are highly necessary in today's workforce. Technology also enables increased accessibility and flexibility in learning, allowing learners to study anytime and anywhere. Collaboration and communication between tutors and learners, as well as among the learners themselves, can be enhanced through online platforms and digital collaboration tools. With a deep understanding of content andragogy technology, tutors can create more effective, efficient, and engaging learning experiences, helping adult learners better achieve their learning goals.